The Second-Order Sliding Mode Control Algorithm for Fixed-Time Stability of Nonlinear Systems - Zeng, Qinjun; Jiang, Minghui; Hu, Junhao (Circuits, systems, and signal processing, 2024)
This article focuses on the fixed-time stability of a class of nonlinear systems with uncertain disturbances and time-varying delays. Different from other papers, the second-order sliding mode control algorithm (SOSMCA) is developed in this article to study the fixed-time stability of nonlinear systems for the first time. Additionally, the novel sliding mode surface (SMC) and second-order SMC are presented. And the stability and reachability of the sliding-mode dynamics under a faster settling time are demonstrated. Finally, the applicability and validity of the obtained SOSMCA are demonstrated by a simulation example with the F-404 aircraft engine model.